Association of Child-Pugh Score with Renal Dysfunction in Liver Cirrhosis Patients - Utomo, Edrick; Siregar, Gontar Alamsyah (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background Renal dysfunction remains a common and serious complication in cirrhotic patients and affecting the prognosis of the patient. Early prevention, diagnosis, and treatment are important to avoid any morbidity and mortality caused. This study aims to evaluate the association between the Child-Pugh score and its parameters with renal dysfunction in liver cirrhosis. Method This study was a retrospective cross-sectional by design. This study was conducted at Adam Malik General Hospital with a total sampling of liver cirrhosis inpatients in January 2017-December 2018 periods. Result Total 259 patients were included with data collected from the medical record. The results of statistical analysis with Chi-square and Fisher’s Exact founded an association between Child-Pugh (p=0.003) and ascites (p=0.014) with renal dysfunction in liver cirrhosis patients. Meanwhile, hepatic encephalopathy was not found in an association with p-value=0.144. Mann-Whitney test used to evaluate median differences of albumin, bilirubin and international internalized ratio (INR) in groups of liver cirrhosis with and without renal dysfunction. The results, albumin was found significant differences with p-value=0.017. Bilirubin and INR were found no significant differences (p>0.05). Conclusion It was concluded association found between Child-Pugh score with renal dysfunction in liver cirrhosis patients.